Establishing a Master׳s for Europe – A transnational model for higher education. (February 2016) - Fleming, V.; Luyben, A.
Abstract: Background and context: Over the last 50 years leading international organisations have been emphasising the key role that midwives play in the provision of quality care for women and babies throughout the pregnancy continuum. Midwifery education, however, generally remained at pre-university level until recently when Bachelors' programmes were developed. In Europe this development was taken further with the awarding of a European Union Lifelong Learning Programme grant to a consortium of five universities in four countries to develop a joint Master's degree in midwifery. The first students, drawn not only from the countries of the partner institutions but also from other European countries and from countries outside of Europe, commenced their studies in 2009. Does the programme meet its objectives and those set out in the Lancet series?: The objectives of the programme were in line with the requirements for effective midwifery care and evidence based practice as discussed in the Lancet series. Threats and challenges to sustainability: As an EU funded project all the goals were met. However, in terms of its long-term sustainability problems arose due to the need for universities to rationalise programmes. The number of students has remained steady but low with the projected growth not taking place thus it has been impossible to perceive an impact on midwifery practice and the health of women and children where graduates are working. Conclusion: Despite limitations, the programme serves as an exemplary model of how a Master's programme in midwifery can be successfully built through a collaboration of interested parties from different countries, and can be applied at a global level in other regions of the world, with sufficient political and economic support.